Intermittent therapy with levosimendan in patients with advanced heart failure. (14th October 2021) - Blaschke, M; Kiwi, A; Hagl, C; Weis, M
Abstract: Introduction: Therapeutic options for patients with advanced heart failure on the high-urgent (HU) heart transplant (HTx) waiting list are limited. In view of the limited data on the usefulness of classic inotropes, the calcium sensitizer levosimendan (Lev) may be a possible alternative for patients in need of a repetitive therapy with an inotropic agent as a bridge to HTx. Method: In a single-center open-label study we retrospectively analyzed data from 34 HU-listed patients (from a total collective of 95 HU patients) who repetitively received Lev (12.5 mg; 0, 05–0.1 μg/kg/min over 24–48h) in 2–8 weeks intervals due to cardiac instability and/or progressive second organ dysfunction. Potential side effects as well as changes of kidney, liver and heart functional parameters were evaluated (0–6 days before, 4–8 days and 14–20 days after Lev infusion). Patient collective: age 51±10 years, 6 women, 28 men; NYHA stage III-IV. 11 Patients with ischemic cardiomyopathy (32%), 19 patients with dilated cardiomyopathy (56%), 4 patients with arrhythmogenic right ventricular cardiomyopathy (12%). Results: The waiting time for HTx was up to 12 months (6±5 months). There were no adverse, serious events (resuscitation, defibrillation for ventricular tachycardia (VT), intubation and ventilation, renal replacement therapy) up to 7 days after Lev infusion. Transient cardiac arrhythmias (ventricular bursts or non-sustained VTs) occurred in 11 patients (32%) with spontaneous termination and no need of urgent anti-arrhythmic therapy. The values for sodium, potassium, Hb and CRP did not change significantly after Lev. In contrast, there was a significant reduction in creatinine after 4–8 days (initially 1.43±0.4 mg/dl; after 4–8 days 1.28±0.3; p<0.0005) with an increase again after 14–20 days (1.43±0.3 mg/dl). The bilirubin value was significantly reduced after 4–8 days (initially 1.63±0.7 mg/dl; after 4–8 days 1.30±0.5; p<0.0005) with only partial (non-significant) increases again over the course (1.34±0.5 mg/dl). The BNP value was significantly reduced 4–8 days after administration of Lev (initially 1565±1136 ng/l; after 4–8 days 1103±895; p<0.0001) and increased again in the longer time course (1462±1001 ng/l; p<0.001 versus 4–8 days). 28 patients were successfully transplanted (82%). 6 patients remained without HTx (18%), of which 1 patient (3%) with clinical improvement could be discharged. 2 patients (6%) received an LVAD and 3 patients (9%) died during the waiting period. Conclusion: Intermittent therapy with Lev as "a bridge to transplant" is safe and effective concerning deterioration of heart failure and prevention of progressive kidney/hepatic dysfunction. However, a prospective randomized multi-center trial is necessary to underscore the encouraging data of this observational, single center study. Funding Acknowledgement: Type of funding sources: None.